Examining the use of instructional video clips for teaching macroeconomics. - Expósito-García, Alfonso; Sánchez-Rivas, Javier; Gómez-Calero, María Palma; Pablo-Romero, María (Elsevier, 2020)
Information and communication technologies (ICTs) have been integrated in teaching activities to develop new learning environments. Within ICTs, the use of multimedia, such as instructional videos, has attracted significant academic attention. Nevertheless, the use of these technologies in teaching economics has generally lagged behind other disciplines. This paper adds empirical evidence to show the effectiveness of the use of instructional videos in the field of economics. Firstly, videos illustrating dynamic graphical representations of macroeconomic processes have been developed and used in the class of one student group at the University of Seville (Spain), as complementary teaching materials in the macroeconomics curriculum. Secondly, the effectiveness of these videos has been tested by carrying out an inferential analysis on experimental and control groups. Potentially significant variables such as gender, prior knowledge and ability levels of students have been considered in the analysis. Additionally, probit and multinomial probabilistic regressions have been estimated in order to assess the impact of these materials on the probability of achieving higher test scores. The findings confirm the superiority of using instructional video-clips to achieve higher test scores.
https://openpolicyfinder.jisc.ac.uk/id/publication/27886
Keywords: Enseñanza - Innovaciones; Macroeconomía - Estudio y enseñanza superior; Instructional video; Teaching; Macroeconomics; Inferential analysis